Initiatives on indigenous fruits in the Philippines: A scoping study - Oraye, Claudette; de Chavez, Hidelisa; Aguilar, Catherine; Makiling, Florisa; Ladia, Villamor Jr.; Enicola, Elmer; Guevarra, Luisa; Gueco, Lavernee; Maghirang, Rodel; Anunciado, Ma; Oro, Emilita; Gonsalves, Julian Francis; et al. (2023)
Despite their potential to diversify diets and improve nutrition, little is known about the consumption and utilization of indigenous fruits (IFs) in the Philippines. This desk review compiles and analyses different initiatives targeting the conservation and promotion of these lesser-known fruits, based on secondary data that were gathered from published and unpublished literature between 2012 to 2022. Most of the literature gathered focused on the evaluation of the functional properties of IFs and product development. Initiatives are also present in germplasm collection and conservation of IFs, characterization and assessment of diversity, variety development, evaluation of nutritional quality, and various promotional activities to increase awareness of these fruits. This study led to the identification of some IFs for conservation, promotion and further studies based on their potential in contributing to health and wellness, as well as their market potential. It also identified several issues and knowledge gaps in initiatives and research on IFs that need further investigation to better incorporate IFs in the local food system.